2011
DOI: 10.1111/j.1365-2095.2010.00841.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of dietary selenium on growth performances, oxidative stress and tissue selenium concentration of gibel carp (Carassius auratus gibelio)

Abstract: A 100-day growth trial was executed to determine the dietary selenium (Se) requirement of juvenile gibel carp (Carassius auratus gibelio). Selenomethionine was supplemented to casein-gelatin diets at 0, 0.1, 0.25, 0.5, 1.0, 2.5 and 5 mg

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
81
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(90 citation statements)
references
References 47 publications
9
81
0
Order By: Relevance
“…Supplementation of Se may increase growthrelated gene expression in yellowtail kingfish. In the present study, the beneficial growth effect of dietary Se for yellowtail kingfish was shown by the weight gain data and this is consistent with the data reported for grouper (Epinephelus malabaricus) [21], cobia (Rachycentron canadum) [22] and gibel carp (Carassius auratus gibelio) [23]. The optimal Se requirement for maximal growth of yellowtail kingfish obtained from our study is higher than that reported for other fish species [21][22][23].…”
Section: Discussionsupporting
confidence: 92%
“…Supplementation of Se may increase growthrelated gene expression in yellowtail kingfish. In the present study, the beneficial growth effect of dietary Se for yellowtail kingfish was shown by the weight gain data and this is consistent with the data reported for grouper (Epinephelus malabaricus) [21], cobia (Rachycentron canadum) [22] and gibel carp (Carassius auratus gibelio) [23]. The optimal Se requirement for maximal growth of yellowtail kingfish obtained from our study is higher than that reported for other fish species [21][22][23].…”
Section: Discussionsupporting
confidence: 92%
“…Selenium deposition in liver increased linearly with increasing levels of dietary selenium. This linear increase has been described in multiple fish species, regardless of the source of Se, including Atlantic salmon (Berntssen et al, ), black sea bream (Wang et al, ), channel catfish (Wang & Lovell, ), cobia (Liu et al, ), gibel carp (Han et al, ), hybrid striped bass (Cotter, Craig, & Mclean, ), malabar grouper (Lin, ), Nile tilapia ( Oreochromis niloticus , Lee, Nambi, Won, Katya, & Bai, ), olive flounder ( Paralichthys olivaceus , Lee, Lee, Bai, & Hung, ), rainbow trout (Hilton & Hodson, ; Wang et al, ) and white sturgeon (Tashjian et al, ). Dietary Se may also affect the deposition of other minerals in liver, such as copper, which follows a positive correlation with Se deposition in Atlantic salmon (Poppe, Håstein, Frøslie, Koppang, & Norheim, ) or rainbow trout (Hilton & Hodson, ).…”
Section: Discussionmentioning
confidence: 81%
“…(). Feeding juvenile rainbow trout with 4.6 mg organic Se/kg diet for 90 days significantly reduced weight gain and fishtail fork length (Vidal et al., ), while feeding gibel carp with 5 mg organic Se/kg diet for 100 days did not reduce growth (Han et al., ).…”
Section: Discussionmentioning
confidence: 99%